Effects of Serum Metabolites on the Pancreatic Transcriptome in Acute Acalculous Cholecystitis. (8th December 2021) - Sun, Yuanyuan; Wang, Qiang; Hao, Chenjun; Xue, Dongbo
Abstract : Background . To provide a basis for the diagnosis and treatment of acalculous biliary pancreatitis, this study investigated the impact of serum metabolites on the pancreatic transcriptome in acute acalculous cholecystitis (AAC). Methods . Fourteen rabbits were randomly divided into two groups (a normal control group of 7 rabbits and an AAC group of 7 rabbits), blood was collected from the 14 rabbits, and metabolomic analysis was performed through 1 H NMR. Two pancreatic tissue chips of the AAC group and the normal control group were prepared and sequenced. We utilized the limma package of R software, the DAVID database, the STRING database, Cytoscape software, and the CFinder analysis tool to perform differential expression gene analysis, gene function enrichment analysis, protein interaction network (PPI) construction, and network module mining, and we performed gene enrichment analysis in each module. Results . Serum metabolism analysis showed that in AAC, the metabolism of sugar, lipids, and protein, that is, the three major nutrients, was affected to varying degrees, and levels of serum trimethylamine N-oxide (TMAO) increased. Bioinformatic methods were utilized to identify a total of 183 differentially expressed genes and 3 key genes. Enrichment analysis showed that differentially expressed genes were significantly enriched in cation transport, the inflammatory response, the NF- κ B pathway, and the cancer signaling pathway. Conclusion . Metabolomic analysis and functional analysis of 3 key genes demonstrated that abnormal serum metabolites affected the pancreatic transcriptome and induced a sensitive state of inflammation in the pancreas. These metabolites may represent important targets for future research on the pathogenesis, clinical diagnosis, and treatment of noncalculous biliary pancreatitis.